I INSEKTA PENGUNJUNG CABAI MERAH (Capsicum annuum L.) DAN SUMBANGSIHNYA PADA MATERI INSEKTA KELAS X SMA/MA - Putri, Mutia Belian; Wahidi, Ismed; Zural, Mimin Mardhiah (Jurnal Bioconcetta, 2019)
The aims of this research to find out the kind of insects that visited red chili inblooming phase to be used a validity of teaching material. This research isdevelopment research by descriptive with the method of collecting insects thatvisited red chili and development research with 4D models that modifiy fromThiagarajan et al., (1975), arrive developt phase which is expert judge. Thedata was processing and analyzed with qualitatively and descriptive. Basedon the research from type of goer insects, it was found there are 14 species.With results from development research was found criteria very valid(83,1%). Related to this research it can be concluded that types of goerinsects for red chili which contribute to atlas in role of insects for plantstopics is reasonable.